The impact of temperature and sediment resuspension on microbial eukaryote recruitment from shallow Baltic Sea sediment - Sassenhagen, Ingrid; Herlemann, Daniel P. R.; Gentsch, Kaja; Kremp, Anke; Labrenz, Matthias; Dutz, Jörg (Frontiers in Microbiology, 2025)
Germination from plankton resting stages is often inhibited by burial and anoxic conditions in the sediment. Resuspension of surface sediments by storms might, therefore, represent an important mechanism that facilitates germination. We investigated the impact of sediment resuspension on the composition of planktonic microbial eukaryote community, assessed through 18S rRNA gene metabarcoding, by incubating sediment cores from Greifswald Bay (Baltic Sea) either undisturbed or with regular resuspension events for 4 months at rising temperatures. In this experiment, the planktonic eukaryotic community composition was mostly characterized by temporal species succession likely driven by the gradual increase in water temperature. Furthermore, NO3− concentrations and sediment resuspension were identified as important factors shaping the eukaryotic community composition. Nitrate concentrations were significantly higher in the control than in the mixed sediment cores, as resuspension likely caused a significant loss of nitrate to the sediment. Unexpectedly, eukaryotic alpha diversity was not significantly altered by mixing, but the community composition changed due to the germination of previously buried species. These results highlight the importance of sediment resuspension for the activation of buried resting stages and for altering nutrient concentrations in the water column impacting planktonic microbial community composition.